ACCEPTANCE TOWARD CHILDREN AND FATHERING IN CARING FOR CHILDREN WITH HEARING IMPAIRMENT - Kusnadi, Starry Kireida; Agustin, Ardianti (Faculty of Psychology, Diponegoro University, 2020)
Â The purposes of this research are to observe acceptance toward children and father role in caring for children with hearing impairment. Acceptance is someoneâ€™s process in accepting reality, accept others as they are overall, have a positive gesture toward others, admit and accept various aspects, including the bad and good qualities. Father who fully involved in caring children will give positive impacts on whole aspects of child development. This research applies to the quantitative method. The scale used is acceptance toward children scale and father involvement scale. The subjects in this research are 37 father who has children with hearing impairment. Research result shows that there is a significant relation between acceptance toward children and father involvement in caring for children with hearing impairment (r = 0,948 ; p < 0,001). Therefore, the higher the acceptance toward children with hearing impairment is, the higher the fathering involvement can be concluded.Â